The The Effect of Prone Positioning to Increase Oxygen Saturation in Covid-19 Patients at Hermina Banyumanik Hospital - Intan Nurani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
The coronavirus disease 2019 (Covid-19) pandemic is still a problem for many countries in the world. One of the symptoms of Covid-19 patients is respiratory disorders with clinical signs of pneumonia both mild to severe which is characterized by low levels of oxygen saturation in the body. There is currently no FDA (Food and Drug Administration) approved treatment for Covid-19. In addition, an intervention that can be done to overcome the problem of ineffectiveness of breath patterns is by regulating the position in the patient. One of the supportive and rehabilitative treatments for Covid-19 patients is the prone position. This study was conducted to assess the effectiveness of prone positioning on increasing oxygen saturation in Covid-19 patients at Hermina Banyumanik Hospital. The design used in this study is quasi-experimental design and uses a nonequivalent control group design model. The number of samples in this study was 16 respondents plus 30% to 20 respondents in each group, who were moderate symptomatic Covid-19 patients from June to August 2021. This study used the wilcoxon test with the results of asymp.sig. (2-tailed) is worth 0.000 < 0.05, then it can be concluded that there is an influence of prone position on increasing oxygen saturation. Based on these results, it can be seen that there is an effectiveness of prone position in increasing oxygen saturation in Covid-19 patients at Hermina Banyumanik Hospital.